Gill Structure of Pangasius polyuranodonBleeker,1852 fromthe Sail River, Riau Province - Yohana Carolina; Windarti Windarti; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractSail River is a polluted river in Riau, however, many types of fish, including catfish Pangasius polyuranodonBleeker (1852) is living in that river. The water condition of the river may effect the fish health status in general, including its gill structure. A study aims to understand the histological structure of the gill of that fish has been conducted in February-March 2018. Abnormality in the gill was noted and abnormality level was identified using a Histopathological Alteration Index (HAI). Results shown that the types of abnormality present were hyperplasia/cell proliferation, hypertrophy, odema or swelling, atrophy, blood vessel congestion, hemorrhage, and ruptured epithelium. The minimum HAI value obtained is 0.142, and maximum value is 1.857 ( average 1.031), indicates that the gill of P. polyuranodon from the Sail River is categorized as less damage. Keywords: Histopathological Alteration Index (HAI), gill abnormality, polluted river, Catfish